3(7a+3)=4(a+12)

Simple and best practice solution for 3(7a+3)=4(a+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7a+3)=4(a+12) equation:



3(7a+3)=4(a+12)
We move all terms to the left:
3(7a+3)-(4(a+12))=0
We multiply parentheses
21a-(4(a+12))+9=0
We calculate terms in parentheses: -(4(a+12)), so:
4(a+12)
We multiply parentheses
4a+48
Back to the equation:
-(4a+48)
We get rid of parentheses
21a-4a-48+9=0
We add all the numbers together, and all the variables
17a-39=0
We move all terms containing a to the left, all other terms to the right
17a=39
a=39/17
a=2+5/17

See similar equations:

| |x+4=10 | | 4/7x-5/3=(3x+1)/2 | | 2(5+5v)=90 | | 45x+-720+15x=60 | | |8x-7|+14=10 | | 5m^-22m+8=0 | | 3/y=15/10 | | 2x+18=8x+20 | | 2(x−6)+14=38 | | 97-34+10y-3=180 | | (x+1)(x-2)=70 | | 6x^2+8x=8 | | (x)/(4)=-45 | | m²-16=0 | | 24-x=1/3 | | 10x^2+29x-10=0 | | 5x+10+3x+10=4x+30 | | 3x+2/4=x-5 | | -3(j-7)+5=-1 | | 9-3a=8a-2 | | 11=1-8m-2m | | 2x^-x=15 | | -4k+14=-3k-3 | | -2+x/8=-4 | | 2(2k-7)=-3k-3 | | 6x+2-4x+7=37x=14 | | 5x+6-3x+14=2x-18 | | |9x-8|=|2x-11| | | -24-13n=-8n | | 25x+(9x+10)=180 | | 22-(x+8)=(8x-4) | | 20x+5x=65 |

Equations solver categories